For the commutation relation in quantising the bosonic string


we can then calculate this for $m=-n$ in between the vacuum state i.e.

$$\boxed{\left<0,0|\left[L_n,L_{-n}\right]|0,0\right>=\frac{D}{2}\sum_{m=1}^{n-1}m(n-m)\left<0,0|0,0\right>=\frac{D}{12}n(n^2-1)\left<0,0|0,0\right>} \, .$$

The second expression I can't seem to show explicitly although I know we can can write


and then it's surely something to do with how these $\alpha$'s act on the vacuum state. However, why the $m(n-m)$ and where's the $\frac{D}{2}$ come from?

Finally, the last term in the boxed calculation is obviously found from the commutation relation of $\left[L_n,L_{m}\right]$, but therefore $\left<0,0|L_0|0,0\right>=0$. Why is this?


closed as off-topic by ACuriousMind, Kyle Kanos, Gert, Danu, yuggib Mar 18 '16 at 14:18

This question appears to be off-topic. The users who voted to close gave this specific reason:

  • "Homework-like questions should ask about a specific physics concept and show some effort to work through the problem. We want our questions to be useful to the broader community, and to future users. See our meta site for more guidance on how to edit your question to make it better" – ACuriousMind, Kyle Kanos, Gert, Danu, yuggib
If this question can be reworded to fit the rules in the help center, please edit the question.


To show: $$\boxed{\left<0,0|\left[L_n,L_{-n}\right]|0,0\right>=<0,0|n^2L_0+\frac{D}{2}\sum_{m=1}^{n-1}m(n-m)\left|0,0\right>=<0,0|\frac{D}{2}\sum_{m=1}^{n-1}m(n-m)\left|0,0\right>= \frac{D}{2}\sum_{m=1}^{n-1}m(n-m)\left<0,0|0,0\right> = \frac{D}{12}n(n^2-1).}$$

Why is the first term vanishing?

To see that $\left<0,0|n^2L_0|0,0\right> =0$ one can use the algebra commutator relation and write $$ 2 L_0 |0,0 \rangle = (L_1 L_{-1} - L_{-1} L_1) |0,0\rangle =0 $$ as done in Polchinski, p 59. The expression is zero, because the $L_{\pm 1}$ can be viewed as normal ordered $$L_n=\frac{1}{2}\sum_{n=1}^{\infty} : \alpha_{n} \alpha_{-n} :$$ with all annihilation operators to the right destroying the $|0,0 \rangle$.

Why is $\frac{D}{2}\sum_{m=1}^{n-1}m(n-m)=\frac{D}{12}n(n^2-1)$ ?

Let's decompose the sum in 2 terms $$\frac{D}{2}\sum_{m=1}^{n-1}m(n-m) = \frac{D}{2} n \sum_{m=1}^{n-1}m -\frac{D}{2}\sum_{m=1}^{n-1}m^2 $$ The first sum can be identified with one known finite series $\sum_{k=1}^l k =\frac{l(l+1)}{2}$ giving $$\frac{D}{2} n \sum_{m=1}^{n-1}m = \frac{D}{2}n\frac{(n-1)n}{2}.$$ The second sum can be identified with another finite series from the same list $ \sum_{k=1}^l k^2 = \frac{l(l+1)(2l+1)}{6}$ giving $$\frac{D}{2}\sum_{m=1}^{n-1}m^2= \frac{D}{2} \frac{(n-1)n(2n-1)}{6}.$$ Subtracting the second sum from the first one arrives at desired result $$\boxed{\frac{D}{2}\sum_{m=1}^{n-1}m(n-m)=\frac{D}{12}n(n^2-1)}.$$


Not the answer you're looking for? Browse other questions tagged or ask your own question.